Problem Based Learning Strategy for Better Speaking Ability - Saiful Saiful; Hamid Ismail; Rina Asrini Bakri; Maharida Maharida (Celebes Scholar pg, 2022)
The objective of this study was to find out the increase of the students’ speaking ability in SMAN 13 Gowa in mastery, the speaking ability by applying problem-based learning strategy. The research population of this study was the eleventh-grade students of SMAN 13 Gowa in academic year 2020/2021. It consisted of an 8 classes and total populations were 213 students. This research used the purposive sampling technique, and the class IX Social was chosen as the sample of the study. The total of sample were the 24 students. The instrument of this research was speaking test. Speaking test was given as pre-test before doing the treatment to know prior ability of the students and post-test after doing treatment to find out the students’ speaking ability achievement by using problem-based learning strategy. The findings showed in pre-test that mean score of accuracy was 2,42, students’ and the students mean score of comprehensibility was 2,42. The total students’ mean score in pre-test was 4,83. In post-test, the students’ mean score of accuracy was 2,96 and the students’ mean score of comprehensibility was 3,63. The total students’ mean score on post-test was 6,58. It can be concluded that the total mean score of students in post-test was higher than pre-test. The researcher concluded that the use of problem-based learning strategy improves the student’s speaking ability and can be used for better speaking ability.